Alteplase for the Treatment of Pulmonary Embolism: A Review. (October 2015) - Peters, Nicholas A.; Paciullo, Christopher A.
Abstract : Pulmonary embolism can present with a wide range of symptoms, from asymptomatic to cardiac arrest, making diagnosis challenging. Alteplase is a fibrinolytic that is indicated for the treatment of pulmonary embolism in intermediate- and high-risk patients. Controversy exists as to the patient population that will benefit most from fibrinolytic therapy, as well as the proper dose and administration technique. The patient's risk of bleeding should be weighed against the potential benefits of treatment in light of the clinical presentation because of the high mortality rate associated with pulmonary embolism. Nurses at the bedside must monitor for signs of bleeding when alteplase is administered. Fibrinolytic therapy will frequently be started in the emergency department, and the nurse must ensure that alteplase is administered in a safe and effective manner. This review discusses the clinical evidence for alteplase in pulmonary embolism and its specific role in treatment.